2018
DOI: 10.21474/ijar01/6513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyperglycemia on Outcome of Acute Exacerbation of Chronic Obstructive Pulmonary Disease.

Abstract: COPD is a growing cause of morbidity and mortality worldwide, and will be the third leading cause of death by 2020. The Global Initiative for Chronic Obstructive Lung Disease (GOLD) recently defined COPD as "Chronic Obstructive Pulmonary Disease (COPD) is a common, preventable and treatable disease that is characterized by persistent respiratory symptoms and airflow limitation that is due to airway and/or alveolar abnormalities usually caused by significant exposure to noxious particles or gases". [1] Hypergly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…High blood glucose (BG) levels have been associated with increased infection rates, poor wound healing, longer hospital stays, higher treatment costs and higher mortality during hospitalisation [ 5 – 9 ]. In patients with acute exacerbations of chronic obstructive pulmonary disease (COPD), hyperglycaemia has been linked to worse outcomes [ 10 , 11 ]. A meta-analysis showed that intensive glycaemic control was associated with a lower risk of infection in hospitalised patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…High blood glucose (BG) levels have been associated with increased infection rates, poor wound healing, longer hospital stays, higher treatment costs and higher mortality during hospitalisation [ 5 – 9 ]. In patients with acute exacerbations of chronic obstructive pulmonary disease (COPD), hyperglycaemia has been linked to worse outcomes [ 10 , 11 ]. A meta-analysis showed that intensive glycaemic control was associated with a lower risk of infection in hospitalised patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%